Mixtape potluck : a cookbook - Questlove; Greenman, Ben; Schaefer, Lauren (Abrams Image, 2019)
" Questlove is best known for his achievements in the music world, but his interest in food runs a close second. He has hosted a series of renowned Food Salons and conversations with some of America's most prominent chefs. Now he is turning his hand to creating a cookbook. In Mixtape Potluck Cookbook, Questlove imagines the ultimate potluck dinner party, inviting more than fifty chefs, entertainers, and musicians--such as Eric Ripert, Natalie Portman, and Q-Tip--and asking them to bring along their favorite recipes. He also pairs each cook with a song that he feels best captures their unique creative energy. The result is not only an accessible, entertaining cookbook, but also a collection of Questlove's diverting musical commentaries as well as an illustration of the fascinating creative relationship between music and food. With Questlove's unique style of hosting dinner parties and his love of music, food, and entertaining, this book will give readers unexpected insights into the relationship between culture and food"--Amazon.